Light vector meson production in pp collisions at √s=7 TeV* - Abelev, Betty; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physics letters, 2012)
The ALICE experiment has measured low-mass dimuon production in pp collisions at s=7 TeV in the dimuon rapidity region 2.5<y<4. The observed dimuon mass spectrum is described as a superposition of resonance decays (η,ρ,ω,η′,ϕ) into muons and semi-leptonic decays of charmed mesons. The measured production cross sections for ω and ϕ are σω(1<pt<5 GeV/c,2.5<y<4)=5.28±0.54(stat)±0.49(syst) mb and σϕ(1<pt<5 GeV/c,2.5<y<4)=0.940±0.084(stat)±0.076(syst) mb. The differential cross sections d2σ/dydpt are extracted as a function of pt for ω and ϕ. The ratio between the ρ and ω cross section is obtained. Results for the ϕ are compared with other measurements at the same energy and with predictions by models.